Análise de Tendências de Precipitações e Temperaturas Mensais de 1961 a 2008 no Brasil Usando Dados Gradeados (Analysis of Trends of Monthly Precipitation and Temperatures of 1961 to 2008 in Brazil Using Gridded Data) - Costa, Rafaela Lisboa; Silva, Fabrício Daniel dos Santos; Sarmanho, Gabriel Fonseca; Ferreira, Danielle Barros (Revista Brasileira de Geografia Física, 2013)
Este trabalho analisa um conjunto climatológico de dados gradeados de precipitação, temperaturas médias, máximas e mínimas, mensais, de 1961 e 2008. Tendências lineares foram estudadas, identificando-se as áreas onde foram estatisticamente significantes. Tendências positivas, foram verificadas para temperaturas máximas, mínimas e médias, em diferentes intensidades. Em relação à precipitação, as áreas com tendências de aumento ou diminuição alternam-se mês a mês, com padrões menos evidentes do que os das temperaturas. Palavras-chave: temperatura, precipitação, tendências climáticas. Analysis of Trends of Monthly Precipitation and Temperatures of 1961 to 2008 in Brazil Using Gridded Data ABSTRACT This paper analyzes a climatological dataset of monthly grid data of precipitation, average temperature, maximum and minimum temperature, between 1961-2008. Linear trends were studied, identifying the areas where these were statistically significant. Positive trends were observed for maximum, minimum and average temperatures, with different intensities. For precipitation, the areas with increasing or decreasing trend alternate month by month, with patterns less evident than the temperatures. Keywords: temperature, precipitation, climatic trends